Behavioral responses of Canada geese to winter harassment in the context of human‐wildlife conflicts. (27th November 2022) - Askren, Ryan J.; Eichholz, Mike W.; Sharp, Christopher M.; Washburn, Brian E.; Beckerman, Scott F.; Pullins, Craig K.; Fournier, Auriel M. V.; Vonbank, Jay A.; Weegman, Mitch D.; Hagy, Heath M.; Ward, Michael P.
Abstract: Wildlife harassment (i.e., intentional disturbance by humans) is a common nonlethal management approach employed to reduce human‐wildlife conflicts, but effectiveness is often undocumented or uncertain. We evaluated the effect of harassment on Canada goose ( Branta canadensis ) behavior in an urban area during winter. Winter can be a challenging period for waterfowl given limited food availability and greater thermoregulatory costs; thus, we expected that harassment in winter may be more effective than during other portions of the year. We used GPS transmitters equipped with accelerometers to evaluate the effects of harassment, weather conditions, and breeding origin location on goose movements, land cover use, emigration, survival, and behavior. Harassment caused geese to leave the harassment site more often (3.5 times) than on days when not harassed, but geese returned quickly after harassment (1.9 times) than without harassment. Harassment of geese affected specific goose behaviors (foraging, resting, flying, and alert), but effects of harassment were relatively small compared to the effects of weather conditions. Changes in land cover use were impacted by weather conditions, independent of harassment. Our findings suggest that harassment was ineffective at significantly changing site use or behaviors of geese and repeated harassment had diminishing returns. Geese moved to specific land cover resources that serve as sanctuaries (e.g., open waterbodies) during periods of extreme cold to engage in energetically conservative behaviors (i.e., resting). Harassing geese in areas that provide sanctuary during extreme cold periods or the use of lethal management in coordination with targeted harassment may be more effective than harassment alone in urban areas. Abstract : Winter harassment of Canada geese ( Branta canadensis ) in urban parks did not have significant effects on the use of urban greenspaces or behavioral time budgets. Instead, mean daily temperature and snow cover were the primary driver of greenspace use and behavioral time budgets. Harassment at sites primarily used for resting rather than feeding may be more effective.